Environmental influence on preterm and term infants over rolling movement. - Ferreira, Fabíola Karla Teixeira de Andrade; Almeida, Rafaela Martins de; Rocha, Michelli Aline da; Fambrini, Danilo Luiz; Antonio, Tiago Del; Silva, Joyce Karla Machado da (Manual Therapy, Posturology & Rehabilitation Journal, 2014)
Introduction: Over a lifetime constant changes occur in the complexity and quality of the execution of motor actions, characterizing the motor development. External (environmental) factors may act positively or negatively in the course of some motor skill, such as the ability of rolling. Objective: It is about an analytical cross-sectional study aimed to analyze the positioning of the cradle of preterm and terms infants relating to the rolling movement. Method: The sample comprised 27 infants of both genders, divided into two groups (G1 and G2). G1 was composed of 8 premature infants included in a motor stimulation project and G2 was composed of 19 term infants enrolled in a nursery school. A questionnaire was sent to parents/caretakers and later a practical assessment was held in which the rolling motion was stimulated with rattles, three times for each side (left/right), observing the presence or absence of facilitation in this action. Results: It was found that in both groups, most of the cradles were placed with one of the sides against the wall and the statistical analysis of the data indicated a significant correlation to the placement of the cradle in space and the ease of rolling for preterm infants (p<0.05) and terms infants (p<0.01), while the stimulation was performed by the study researcher. Conclusion: Therefore, it was possible to conclude that there was an ease of rolling to the contralateral side of the wall, i.e. to the side of largest environmental stimulus, which emphasizes the importance of a sensory-rich environment in the course of a proper infant development.